The use of tularemia live vaccine in clinical oncology - Adamyan Robert T.; Galstyan Hairapet M.; Nersesyan Armen K. (Archive of Oncology, 2004)
The review of literature on the use of tularemia live vaccine in clinical oncology is presented. The results of the investigation of tularemia live vaccine as a non-specific stimulator of natural immune and antitumor resistance of patients with endometrial cancer and inoperable lung cancer and its influence on the immunological status of these patients after immunization, during the process of combined treatment, and on long-term (up to 5 years) follow-up after vaccination are shown. A single immunization with tularemia live vaccine increases the main immunological indices in patients with endometrial cancer and inoperable lung cancer already in 2 to 3 weeks after vaccination and they remain during the whole term of follow-up. Moreover, the vaccine shows not only immunostimulating but immunomodulating effect as well and does not give any serious local or general complications. It is shown that due to these effects immunization of patients with tularemia live vaccine in 15 to 20 days before surgery or chemotherapy is followed by a significantly decreased frequency of postoperative complications and better survival. On the basis of the data obtained the authors recommend to use tularemia live vaccine in the complex treatment of those cancer patients who have deep decrease of immunological reactivity.